Upaya Promotif Aktivitas Fisik Pada Komunitas Lansia Di Wilayah Puskesmas Banyuanyar Kota Surakarta - Khairi Rizqi Fadhlika; Umi Budi Rahayu; Seliana Sinta Debi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Physical activity is body movement produced by skeletal muscles that requires energy expenditure to carry out physical activities. When you are elderly, a degenerative process occurs which can put you at risk of disease and injury resulting in a decline in aspects of your health status. The thing that needs to be considered in this condition is the importance of the quality of life of the elderly in an active and effective manner, one of which is physical activity which is related to physical well-being. Based on the results of a survey in the elderly community, namely Pos Lansia Seruni RW 08, Sumber sub-district, it was found that most of the elderly population has low daily activity. The aim of this community service is to promote physical activity in the elderly so that they can improve their functional abilities independently and efficiently and effectively in everyday life. The method used for counseling is promotional and provides media that can be read and taken home in the form of leaflets containing efforts to promote physical activity in the elderly community in the Banyuanyar community health center area, precisely at the Seruni Elderly Post RW 08, Sumber Village, Surakarta City. The results obtained are that the elderly understand and can apply promotional efforts regarding the importance of physical activity.